THE BLOCK MAPS UNIFICATION STUDIES OF PROPERTY TAX IN TWO-DIMENSION CARTESIAN COORDINATE SYSTEM BY USING QUICKBIRD IMAGERY - SISWANTO (NIM 25106025), EKO
The existing property tax geographic information system map in establishment involves a rubber-sheeting manual thus the resulting information is insignificant. In order to unify the map and improve of quality Property tax geographic information system map required new resource such as large scale map includes the land registration map of National Land Agency, orthography map as well as redigitation on property tax block maps then makes transformation for all. Reference surface used for map transformation in unify the property tax block map are rectified Quickbird Imagery using Affine Model. An accuracy level of the land by property tax geographic information system map in research area with tolerance limit 10% of actual size about 18.89% under land registration map of BPN and orthography as new resource; by redigitation and Helmert transformation in block map the accuracy of area in wide can increased to 52.4% with transformation RMSe level between 0.868-4.822.